2015
DOI: 10.1002/2014jd022999
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for vegetation height and wind direction to correct eddy covariance measurements of energy fluxes over hilly crop fields

Abstract: As agricultural hilly watersheds are widespread throughout the world, there is a strong need for reliable estimates of land surface fluxes, especially evapotranspiration, over crop fields on hilly slopes. In order to obtain reliable estimates from eddy covariance (EC) measurements in such conditions, the current study aimed at proposing adequate planar fit tilt corrections that account for the combined effects of topography, wind direction, and vegetation height on airflow inclinations. EC measurements were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 69 publications
6
15
0
Order By: Relevance
“…First, the combined effects of hilly topography and wind direction induced changes in airflow streamlines and turbulent fluxes [23]. Second, when observing fluxes at the field scale in the same study area, [21] and [22] reported the existence of two dominant wind directions, and demonstrated the necessity to discriminate these two wind directions when processing the EC data. Thus, the gap filling methods are likely to provide different relationships between ancillary information and flux measurements, when considering different wind directions.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…First, the combined effects of hilly topography and wind direction induced changes in airflow streamlines and turbulent fluxes [23]. Second, when observing fluxes at the field scale in the same study area, [21] and [22] reported the existence of two dominant wind directions, and demonstrated the necessity to discriminate these two wind directions when processing the EC data. Thus, the gap filling methods are likely to provide different relationships between ancillary information and flux measurements, when considering different wind directions.…”
Section: Introductionmentioning
confidence: 95%
“…These tests permitted to ensure that the theoretical requirements for the EC measurements were fulfilled [27]. On the same site, [21,22] applied these tests over EC datasets collected under conditions of hilly topography, and reported good energy balance closure for the selected data. We kept the high and good quality classes as defined by [28] and [29], since these two classes are considered as suitable for long-term observations.…”
Section: Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The main potential drawback of the double rotation method is that a significant variability in rotation angles can be observed at low wind speeds (Turnipseed et al, 2003). Since our study area was typified by large wind speeds (Zitouna-Chebbi et al, 2012, 2015, we selected the double rotation method that is applied to each time interval over which the convective fluxes are calculated (30 min in our case). After a first rotation (yaw angle) that cancels the lateral component of the horizontal wind speed, a second rotation (pitch angle) is applied around a horizontal axis perpendicular to the main wind direction to cancel the mean vertical wind speed.…”
Section: Coordinate Rotationsmentioning
confidence: 99%